Dopaminergic and other genes related to reward induced overeating, Bulimia, Anorexia Nervosa, and Binge eating. Issue 1 (2nd January 2022) - Blum, Kenneth; Thanos, Panayotis K.; Wang, Gene -Jack; Bowirrat, Abdalla; Gomez, Luis Llanos; Baron, David; Jalali, Rehan; Gondré-Lewis, Marjorie C; Gold, Mark S
ABSTRACT: Introduction: Eating Disorders and Obesity are a primary global public health concern. Areas Covered: This article aims to trace the neurochemical mechanisms of unwanted eating disorders and target specific loci, within the Brain Reward Cascade (BRC) for therapeutic interventions. Changes due to BRC polymorphisms in functional connectivity and neurotransmission can manifest as overeating, Bulimia Nervosa, and Anorexia Nervosa, and other related eating disorders. Expert opinion: Variations in dopamine function within the Ventral Tegmental Area (VTA), Nucleus Accumbens (NAc), and Ventral Striatum of individuals result in different outcomes related to maladaptive eating behaviors. The goal is to reduce maladaptive eating behaviors by implementing novel strategies that induce Dopamine Homeostasis within the BRC. Clinicians determine genetic risk severity and identify polymorphic targets for either pharmaceutical or nutraceutical interventions. Precision neuro-nutrient formulations of KB220 (Research ID Code) matched precisely to deficient neurotransmitter systems may promote the long-term development of 'dopamine homeostasis' to treat and prevent overeating, Bulimia, and Anorexia Nervosa.